Kinetics of Acetate Utilization by Two Thermophilic Acetotrophic Methanogens: Methanosarcina sp. Strain CALS-1 and Methanothrix sp. Strain CALS-1 - Min, Hang (1989)
The kinetics of acetate utilization were examined for washed concentrated cell suspensions of two thermophilic acetotrophic methanogens isolated from a 58°C anaerobic digestor. Progress curves for acetate utilization by cells of Methanosarcina sp. strain CALS-1 showed that the utilization rate was concentration independent (zero order) above concentrations near 3 mM and that acetate utilization ceased when a threshold concentration near 1 mM was reached. Acetate utilization by cells of Methanothrix sp. strain CALS-1 was concentration independent down to 0.1 to 0.2 mM, and threshold values of 12 to 21 μM were observed. Typical utilization rates in the concentration-independent stage were 210 and 130 nmol min(−1) mg of protein(−1) for the methanosarcina and the methanothrix, respectively. These results are in agreement with a general model in which high acetate concentrations favor Methanosarcina spp., while low concentrations favor Methanothrix spp. However, acetate utilization by these two strains did not follow simple Michaelis-Menton kinetics.